Physicochemical and Heavy Metals Assessments of Leachates from Aperin Abandoned Dumpsite in Ibadan City, Nigeria - G. O. Adewuyi; M. A. Opasina (E-Journal of Chemistry)
Leachates from Aperin dumpsite and control site in Ibadan city, were analysed for physicochemical properties and heavy metals levels. These parameters were compared with control samples and established international standards (FEPA) and (WHO). The dumpsite leachates contained very high concentration of TDS (2436±1035 mg/L) and significant concentrations of COD (395±135 mg/L), BOD (170±33 mg/L), Alkalinity (1157±995 mg/L), Cl- (943±175 mg/L), NO3- (0.66±0.22 mg/L) PO4-(1.98±0.89 mg/L). High concentrations of Iron, Manganese, Copper, Zinc, Nickel, Cadmium and Lead were also observed. All, the parameters were above control and exceeded FEPA and WHO guidelines. The study revealed that this dumpsite is a major polluting source in the surrounding environment. This underlines the need for appropriate government agency Oyo State, Nigeria to initiate an active remediation process such as phytoremediation in combination with physicochemical methods to recover the dumpsite from contaminants and reduce the level of pollution in the surrounding environment.